Between L'Irréparable and l'Irrepérable: Subject to the Past - Downing Thomas; Steven Ungar (Studies in 20th & 21st Century Literature, 1999)
This issue of STCL grew from papers presented at a conference, "Memory in Context: Occupation and Empire in France and the Francophone World," held at the University of Iowa in April, 1996...
Keywords: colonialism; colonial identity; postcolonial identity; hexagonal France; historical studies; literary studies; 1940-44 occupation; power; discourse; identity; memory; l' irréparable; l' irrepérable; resoration